2015
DOI: 10.1007/s00464-015-4566-2
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of symptomatic anastomotic leakage following laparoscopic and open low anterior resection for rectal cancer: a propensity score matching analysis of 1014 consecutive patients

Abstract: The rate of symptomatic AL was comparable following laparoscopic and open LAR in this large, multicenter, cohort study after PSM. Male gender was associated with an increased risk of symptomatic AL after laparoscopic LAR.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
44
1
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 55 publications
(47 citation statements)
references
References 26 publications
1
44
1
1
Order By: Relevance
“…Rectal transection using the laparoscopic approach is a difficult technique that requires much skill; any mistakes during the procedure could directly lead to AL. Previous studies have proposed several potential risk factors for AL including male sex, transanal tube insertion, tumor location, operative time, tumor size, recompression before stapler firings, and BMI . In this study, we identified two risk factors associated with AL occurrence: male sex and AV distance ≤7 cm.…”
Section: Discussionmentioning
confidence: 87%
“…Rectal transection using the laparoscopic approach is a difficult technique that requires much skill; any mistakes during the procedure could directly lead to AL. Previous studies have proposed several potential risk factors for AL including male sex, transanal tube insertion, tumor location, operative time, tumor size, recompression before stapler firings, and BMI . In this study, we identified two risk factors associated with AL occurrence: male sex and AV distance ≤7 cm.…”
Section: Discussionmentioning
confidence: 87%
“…In addition, a lower tumor position increases the difficulty of the operation. Excessive intraoperative blood loss would not only affect postoperative healing but also affects the difficulty of performing the procedure in the surgical field . The change in immune function caused by blood loss may also be one of the potential mechanisms that affects AL.…”
Section: Discussionmentioning
confidence: 99%
“…Surgery is an effective treatment for colorectal cancer (CRC) (1,2), and certain procedures, such as low anterior resection and intersphincteric resection for lower rectal cancer, require an ileostomy to reduce the risk of severe anastomotic leakage (3)(4)(5). High-output ileostomy (HOI) is often observed and is accompanied by electrolyte abnormalities and/or stoma complications (6)(7)(8).…”
Section: Introductionmentioning
confidence: 99%